Racial stratification in self-rated health among Black Mexicans and White Mexicans - Marquez-Velarde, Guadalupe (SSM Popul Health, 2019)
How do Mexicans of distinct racial backgrounds fit into the recognized patterns of racial health disparities? We conduct regression analyses using data from the 2000-2017 National Health Interview Survey to determine if Mexicans who self-identify as White or Black have a relative advantage or disadvantage in self-rated health in relation to Non-Hispanic (NH) Whites and Blacks in the U.S. Our results indicate that both Black Mexicans and White Mexicans have a significant disadvantage in relation to NH-Whites while White Mexicans have a slight advantage in relation to both NH-Blacks and Black Mexicans. Overall, our results suggest that studying health outcomes among Hispanics without considering race may mask inequalities not observed in the aggregate.